The Role of Cultural Identity to Build Social Cohesion: Challenges, Implications, and Integration Strategies in Multicultural Societies - Oluwatosin, Adebayo; Rojak, Jeje Abdul (Metromedia, 2023)
Cultural identity is crucial for building and strengthening social cohesion in multicultural societies. This research aims to analyze the relationship between cultural identity and social cohesion and identify the main challenges that can hinder social integration. The literature review approach examines various theoretical and empirical perspectives from reputable international journals. The results show that cultural identity can serve as a unifying factor that strengthens the sense of social attachment and solidarity in diverse communities. However, there are a number of issues that hinder the contribution of cultural identity to social cohesion, including social polarization, economic inequality, and a lack of inclusive policies that accommodate cultural diversity. In addition, social changes due to globalization further complicate the dynamics of intercultural interactions. Therefore, it is important to further examine the relationship between cultural identity and social cohesion to develop more effective strategies for dealing with diversity. The implications of this research highlight the need for policies that support inclusive cultural integration, an education system that promotes multiculturalism values, and the strengthening of intercultural dialogue to create a harmonious society. Collective awareness of the importance of cultural identity as a cohesive element of society is expected to strengthen social stability and build more harmonious relationships among different groups.